Wittgenstein: Epistemology and Culture - Isenyo Solomon Ogaba (Universitas Negeri Makassar, 2020)
This work assumes that cultures are autonomous and complete within themselves. A particular system is not subject to criticism from the outside. Different cultures have their own systems which are independent of one another. Yet, all these systems and practices are called cultures by virtue of their family resemblance. Different cultures are in contact with one another, and they have to communicate with each other by using their own language-games and systems. When they are in contact with one another they have to reconcile this gap in their communication. Sometimes this can lead to problems in understanding each other. So, in this work, I attempted to make an assessment of these relationships between different cultures and try to give answers to the questions concerning these problems. To do this I gave an interpretation of Wittgenstein's writings on knowledge, most of which can be found in On Certainty.The paper concluded that the nature of the cultural relationships regarding knowledge and belief, and what we can find out from Wittgenstein's ideas on the relationship between different epistemic beliefs,is that they are unique in their own rights,and best understood from their specific cultural epistemic foundations.